(untitled) (Journal of the College of Basic Education, 2022)
The research dealt with an important and vital topic represented by calculating the electrical energy generated from wind speed in Nineveh Governorate and the possibility of investing it to achieve sustainable development, as wind energy is one of the clean alternative energy sources that does not pollute the environment. The wind speed in the study area, where annual average wind speeds were recorded at (1.3, 2.8, 4.4) m / s for the stations of Mosul, Sinjar and Afar respectively, and the amount of electrical energy generated thereof was (1.42, 14.2, 85.2) watts for the three stations respectively, and the highest The seasonal rates of wind speed were during the summer season in all study stations as they reached (1.6, 3.1, 4.6) m / s for the study stations respectively, as this resulted in an increase in the amount of energy generated from them as the electric energy reached (2.64, 41.28, 132.65) watts on The research also found that the Tel Afar station is one of the best stations in which wind energy can be invested due to its geographical location, which is distinguished by the high wind speed compared to the rest of the stations